Propuesta de herramienta de gestión para el reordenamiento territorial de Joyocoto - Sánchez Ortiz, Lenin Adolfo (2023)
The urban growth of Guaranda has led to the loss of agricultural areas in its periphery and boundaries, affecting the production and supply of food, not guaranteeing food security as determined by the Constitution of the Republic of Ecuador, so it is necessary to implement technical tools that allow soil management and agricultural development, In this sense, Joyocoto-Guaranda is located within an agricultural zone, this being its main economic activity, therefore, it is fundamental to establish a management tool, as well as its factors, characterization of the process, from the perspective of the territorial reorganization of Joyocoto, consequently, an explanatory methodology of qualitative and quantitative approach with a descriptive research design is presented. In this order of ideas, the study population corresponds to Joyocoto with 856 inhabitants and an approximate number of 214 houses, belonging to the province of Bolivar, canton Guaranda with a total of 717 lots that represent a study area of 128,46697.5 square meters, which consist of a characterization of properties by areas, finding properties smaller than 200 m2, from 201 to 300 m2, from 301 to 400 m2 and, properties larger than 400 m2, who have suffered subdivisions to orchards and family lots, from the year 2013 to the year 2022. As a fundamental aspect for the collection of information an archival review was made to the Municipality of Guaranda and directly to the Land Management Unit of the Directorate of Planning.